Common Sense and Scientific Inquiry: Remarks on John Dewey’s Philosophy of Educational Progressivism - Malitowska, Anna; Bonecki, Mateusz (ETHICS IN PROGRESS, 2016)
This paper focuses on analysis of relation between pedagogical and epistemological ideas of John Dewey. Our considerations are divided into four sections. (1) We reconstruct Dewey’s conception of culture as a body of normative and regulative common sense beliefs determining human conduct and language use. (2) Further, we compare common sense based inquiry and its scientific mode with regard to their respective conceptual frameworks in order to show that “theoretical-scientific” perspective provides more comprehensive insight into the relations constituting problem situations. (3) We identify informal education with socialization processes and argue that educational process relies on constant reflection on cultural habits. (4) We conclude that competences of using theoretical conceptual frameworks and conducting scientific inquiry play crucial role in Dewey’s educational ideology of progressivism since they provide basic tools for critical reconsideration and revision of common sense beliefs.